Morphological and molecular identification of Diaporthe species in south-western China, with description of eight new species - Wenxiu Sun; Shengting Huang; Jiwen Xia; Xiuguo Zhang; Zhuang Li (MycoKeys, 2021)
Diaporthe species have often been reported as plant pathogens, endophytes and saprophytes, commonly isolated from a wide range of infected plant hosts. In the present study, twenty strains obtained from leaf spots of twelve host plants in Yunnan Province of China were isolated. Based on a combination of morphology, culture characteristics and multilocus sequence analysis of the rDNA internal transcribed spacer region (ITS), translation elongation factor 1-α (TEF), β-tubulin (TUB), calmodulin (CAL), and histone (HIS) genes, these strains were identified as eight new species: Diaporthe camelliae-sinensis, D. grandiflori, D. heliconiae, D. heterostemmatis, D. litchii, D. lutescens, D. melastomatis, D. pungensis and two previously described species, D. subclavata and D. tectonendophytica. This study showed high species diversity of Diaporthe in tropical rain forests and its hosts in south-western China.